Evaluation of Vulnerable age Group of Measles and its Outcome in Under Five Children - Tauhid, Syed Ahsan; Siddika, Syeda Subrina; Anwer, Sk Serjina (Bangladesh Journal of Child Health, 2024)
Background: Measles continues to be a major public health problem worldwide, with a high mortality and morbidity. Unvaccinated young children are at highest risk of measles and its complication including death. Objectives: To assess the vulnerable age group of children for measles under five years of age and also to evaluate the demographic profile, common clinical complication, seasonal variation and outcome of measles among children of Bangladesh. Materials and Methods: This Retrospective observational study was done in the Infectious disease’s hospital, Dhaka during the period of July 2018 to June 2019.The data, were collected, compiled and analyzed. Result: During the study period, a total of 74 confirmed measles cases were selected. Among them, 0-<6-month age group were 21.62%, 6 months to <9 months were 40.54%, 9 months to <15 months were 9.46% and 15 months to <60 months were 28.38%. Highest number of measles cases were admitted in February (14.9%), March (16.2%) and April (14.9%) which are mainly the spring and early summer and lowest in winter. Most common complications of measles were pneumonia and diarrhea. Conclusion: Children below nine month of age who did not reach the vaccination age were found most vulnerable for measles. Occurrence of measles found predominantly in spring and early summer. Pneumonia and diarrhea are the common complications. BANGLADESH J CHILD HEALTH 2022; VOL 46 (2) : 76-81